SELAGINELLA ACTIVE FRACTIONS INDUCE APOPTOSIS ON T47D BREAST CANCER CELL - Handayani, Sri; Risdian, Chandra; Meiyanto, Edy; Udin, Zalinar; Andriyani, Rina; Angelina, Marissa (Indonesian Journal of Pharmacy, 2012)
Apoptosis  is  an  important  target  on  anticancer  mechanism. The  purpose  of  this  research  is  to  investigate  apoptosis  induction of Selaginella plana Hieron active fractions on T47D cells. Absolute ethanol  was  used  to  extract Selaginella  plana powders.  Ethanolic extract  was  dilluted  by  methanol:water  (4:1)  and  then fractionated  by  hexane  (S_Hex),  methylene  chloride  (S_MTC), ethyl acetate (S_EA), and buthanol (S_BuOH). The proliferation of T47D  cell  line  was  detected  by  SRB  (Sulforhodamine  B) assay which  was  measured  at  a  wavelength  of  515nm.  Flowcytometry analysis  to  determine  apoptosis  was  examined  by  Propidium Iodide  (PI)  and  Annexin  V  assay  using  T47D  breast  cancer  cell line.  The  result  showed  that  the  IC50 value  of  S_Hex,  S_MTC, S_EA,  and  S_BuOH  on  T47D  cells  were  107  µg/mL,  4  µg/mL,  6 µg/mL,  and  17  µg/mL  respectively.  The  active  fractions  (S_MTC and  S_EA)  at  its  IC50 concentration  significantly  (P<0.05) increased  the  total  number  of  early  apoptotic  cells  in  the  T47D cells  3.39%  and  4.1%  respectively  compared  to  that  of  control (1.95%).  Based  on  the  result,  methylene  chloride  and  ethyl acetate  fraction  of Selaginella  plana induced  apoptosis  on  T47D cell.Keywords: apoptosis, breast cancer, Selaginella